Winter Oilseed-Rape Yield Estimates from Hyperspectral Radiometer Measurements - Piekarczyk, Jan; Sulewska, Hanna; Szymańska, Grażyna (Quaestiones Geographicae, 2011)
Spectral reflectance data can be used for estimation of plant biophysical parameters such as seed yield, related to the use of solar energy. A field experiment was conducted to investigate relationships between canopy reflectance and seed yield of winter oilseed rape sown on four different dates. Ground hyperspectral reflectance measurements were made using a hand-held radiometer and multispectral images were taken with a VIS-NIR camera. The different sowing dates generated a wide range of difference in crop spectral response and seed yields. The strongest relationships (R2=0.87) between the yield and spectral data recorded by both sensors occurred at early flowering stages. Later, the presence of flowers caused a decline in the relationship between yield and spectral data especially in the visible (VIS) range. In the full flowering stage the strongest correlation (R2=0.72) with the yield showed vegetation indices of the near-infrared (NIR) bands.